2021
DOI: 10.7150/jca.55079
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ZNF460 predicts worse survival and promotes metastasis through JAK2/STAT3 signaling pathway in patient with colon cancer

Abstract: Zinc finger proteins (ZNFs) are a class of protein containing zinc finger domains, and they play an important role in tumor progression. However, as a member of the ZNFs family, the effect of ZNF460 in colon cancer remains unclear. In this study, we found that the expression of ZNF460 protein were markedly increased in clinical colon cancer tissues compared with para-cancer non-cancerous tissues by tissue immunohistochemistry (IHC) and western blot (WB). We also confirmed this result at the mRNA and protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The genes with the highest degree in the Co-DEmiRNA-Gene network include ZNF460 , FBN1 , CDK6 , BTG2, and CBX6 , which may be the essential hub genes/mediators between OSCC and PD. ZNF460 (zinc finger protein 460) is involved in the regulation of multiple cancer processes by JAK2/STAT3 pathway [ 39 ], and its high expression is associated with the proliferation, invasion, and metastasis of colorectal cancer and oral cancer [ 39 , 40 ]. FBN1 (fibrinin-1) is a common extracellular matrix encoding gene [ 41 ], and inactivation will affect the integrity of tissues (aortic wall, periodontal membrane, oral epithelial barrier, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The genes with the highest degree in the Co-DEmiRNA-Gene network include ZNF460 , FBN1 , CDK6 , BTG2, and CBX6 , which may be the essential hub genes/mediators between OSCC and PD. ZNF460 (zinc finger protein 460) is involved in the regulation of multiple cancer processes by JAK2/STAT3 pathway [ 39 ], and its high expression is associated with the proliferation, invasion, and metastasis of colorectal cancer and oral cancer [ 39 , 40 ]. FBN1 (fibrinin-1) is a common extracellular matrix encoding gene [ 41 ], and inactivation will affect the integrity of tissues (aortic wall, periodontal membrane, oral epithelial barrier, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The top5 co-expressed coding genes with XLOC_033882 were SPDYE1, KCNJ13, TBC1D3B, ZNF460, and TAOK1. ZNF460 is a member of the ZNFs family, and overexpression of ZNF460 can predict worse survival in colon cancer ( 51 ). The mechanism of the functions of these four ITIR-lncRNAs needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Literature-based functionality of these 14 DEPCGs showed that several of them were previously implicated in glioblastoma proliferation, invasiveness and treatment resistance ( Supplementary file S3 ), thereby explaining some of the pro-tumorigenic effects of DANCR. For the remaining seven DEPCGs (ZWILCH, RPGR, ZNF460, ZNF528, QTRT2, C5orf15 and CNTRL), no previous functional associations were found with glioblastoma progression, despite a number of them being associated with other cancer types [ 103 , 104 , 105 , 106 , 107 ]. Future investigations into potential previously unaddressed roles of these genes could reveal new players in glioblastoma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%